Actividad antagónica de Trichoderma asperellum (Fungi: Ascomycota) a diferentes temperaturas (2012)
ABSTRACT: The genus Trichoderma (Fungi: Ascomycota: Sordariomycetes: Hypocreaceae) contains species with high antagonistic capacity. It has been determined that the temperature can be a limiting factor for growth of these species. Evaluation in vitro may suggest their eld performance, allowing evidence of viable isolates for use in biological control. In this paper, 27 isolates of Trichoderma spp. were assayed using a dual culture against Rhizoctonia sp. (Fungi: Agaricomycetes) and Colletotrichum sp. (Fungi: Sordariomycetes). From those, 16 and 9 showed an inhibition ≥ 70% against Rhizoctonia sp. and Colletotrichum sp., respectively. The isolates T46, T84, T92, and T109 achieved an inhibition ≥ 75% for both phytopathogens. These isolates were submitted to different temperatures: 4, 10, 15, 20, 25, and 30 °C in order to evaluate their antagonism against Rhizoctonia sp. With the exception of 4 °C, for every temperature assayed the inhibition in growth of the phytopathogen was ≥ 75%. For 30 °C both antagonists inhibited the growth of Rhizoctonia sp.; T46 at 94% and T109 at 95%. Biological activity was shown for all the temperatures, con rming the antagonistic potential of this microorganism.